The effect of individual and environmental factors on internal auditor's risk judgment performance / Fazlida Mohd Razali - Mohd Razali, Fazlida (2019)
Since the growing adoption of Risk Based Internal Audit, the value relevance of internal audit profession rests on their ability to audit risk that is substantial to Board of Director and Management. Revelation of high-profile corporate scandal resulted from internal auditor failures has brought the issues of internal auditor's risk judgment quality and objectivity to the forefront and highly scrutinized. As an insider in organization, internal auditor is highly exposed to conflicts which limit their abilities to excel in risk judgment performances. Studies on internal auditor's performance have concentrated on internal audit department performances rather than individual performances. Utilizing Agency Theory, performances are measured based on the effectiveness of the department as monitoring mechanism in shareholder-manager relationship. Nonetheless, previous study tended to omit the need to study on individual internal auditor's performance as an agent to multi-stakeholders which was not well explained by Agency Theory. Hence, based on Social Cognitive Theory and Bonner's (2008) Judgment and Decision-Making Framework, this thesis addresses this gap by considering the combination effects of individual and environmental factors on internal auditor's risk judgment performance of two task scenarios; easy and difficult. The purpose of this thesis is to answer the question as to what extent does individual factors (experience, conflict management style, internal locus of control, external locus of control and self-efficacy) and environmental factors (external auditor engagement quality, external auditor reliance and social pressure) affect internal auditor's risk judgment performances. In addition, the determinant of self-efficacy as well as the mediating effect of self-efficacy on risk judgment performances is also scrutinized in this thesis. Based on purposive sampling, data were collected through a survey questionnaire sent to six hundred internal auditors from public and private sectors organizations located around Wilayah Persekutuan, Selangor, and Wilayah Persekutuan Putrajaya. A total of two hundred sixty-six internal auditors from public and private sectors participated in the survey. Overall, results of this thesis through the analysis of Structural Equation Model confirmed the effect of experience, self-efficacy and social pressure in risk judgment performances of easy task. Meanwhile, other factors were found to affect internal auditor's risk judgment performances of difficult task. Self-efficacy was found to have mediating effect on risk judgment performances in both easy and difficult tasks. The findings reported in this thesis would be very useful to those in internal auditing profession in the effort to improve the credibility and viability of internal audit profession.